Analysis of the Effect of Tube Current, Slice Thickness, and Tube Voltage on Ct Scan Image Noise using the Noise Power Spectrum (NPS) Method - Kirei, Anggita Ananda; Widita, Rena (Institut Teknologi Bandung, 2023)
This study was conducted to analyze CT scan images in order to determine the effect of tube current, slice thickness, and tube voltage on noise using the Noise Power Spectrum (NPS) method. Moreover, this study was also aimed to identify the optimal range of tube current, slice thickness, and tube voltage values to minimize noise formation in CT scan images while maintaining the safe dose for the patients. The research parameters included variations in tube current values with slice thickness variations, using tube voltages of 80 kV and 120 kV. The tube current (mAs) variations used were 150 mAs, 200 mAs, 250 mAs, 300 mAs, and 350 mAs, while the slice thickness variations were 0.8 mm, 1.6 mm, 3.2 mm, 4.8 mm, and 9.6 mm. A Phillips 16-slice access CT scan with a water phantom was utilized as the material for the research. The obtained image data were analyzed using ImQuest and ImageJ software. The results show that as the variations in tube current (mAs), slice thickness (mm), and tube voltage (mV) increase, the noise values decrease. This was demonstrated by the smallest area under the curve (AUC) values, which were 24.46 variance for the tube current variation at 120 kV and 3.57 variance for the slice thickness variation at 120 kV. Thus, to minimize the noise, it is recommended to increase the tube current, slice thickness, and tube voltage.